Pengembangan Instrumen Penyesuaian Diri Remaja - Khairun, Deasy Yunika; Al Hakim, Ibrahim (Indonesian Journal of Educational Counseling, 2022)
INSTRUMENTS DEVELOPMENT OF ADOLESCENT ADJUSTMENT. The research aims to produce a product in the form of a questionnaire instrument or self-adjustment questionnaire. The product is designed as a tool to identify self-adjustment. The method used is Research and Development. The purpose of research and development is to produce a particular product and test the effectiveness of a product. The stages of developing adolescent self-adjustment instruments are (1) potential problems, data collection, (3) product design, (4) design validation, and (5) usage trials. The results of the trial using the adolescent self-adjustment instrument with 62 statement items resulted in 40 items being declared valid and 22 items being declared invalid.